PANDANGAN KRITIS FILSAFAT PENDIDIKAN ISLAM TERHADAP KONSEP PENDIDIKAN ISLAM PROGRESSIVISME - Aslihah Aslihah; Subhan Subhan; Machdum Bachtiar (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
The purpose of this study is to describe the philosophy of Islamic education, a critical view of the concept of progressive Islamic education. This study uses a literature review to explore relevant concepts. Qualitative descriptive method has been used as a research method. The aim is to monitor the Indonesian education system. These results suggest that the development of an educational philosophy is another school that requires changes in education policy to gain positive self-confidence. There were progressive movements in the modern era, but their rapid development only occurred in the 20th century, especially in the United States. Starring: William James, John Dewey and Johan Heinrich. Actualization in the context of teaching can be seen from several different perspectives, including: the meaning of teaching, teaching objectives, curriculum, learning and the teacher's role in learning. The program is student centered and teachers act exclusively as facilitators, mentors and student development teachers.